(3GdbHS GdMGhj dZQQ VhA GdSNGhis - (3Rjf GdOjf CHi MaU YeQ Hf CMeO Hf Ydj Hf eMehO GdMdHj GdTeGY GdTGaYj GdCKQis; (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s ((3YHO GdQGRb GHf CMeO GdMQjQi GdMdHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi hab CbhGekG ef YHGOg Edi CbJVGA CKQ GaVd s
(3BNQgG (B:s
(3gPG BNQ eG hLOJg ai GdeShOI HNW GdeDda s
(3fSNI LRAGf ai eLdOjfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs